The Effect Of Promotion And Service Quality On Consumer Purchase Decisions Using Delivery Services At J&T Express Drop Point Bintaro South Tangerang - Indrawan, Yossy Wahyu; Jasmani, Jasmani; Triyadi, Triyadi (Universitas Negeri Makassar, 2025)
This study aims to determine the effect of promotion and service quality on consumer purchasing decisions using delivery services at J&T Express Drop Point Bintaro Tangerang Selatan. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study showed that promotion had a significant effect on consumer purchasing decisions by 48.8%, the hypothesis test obtained t count> t table or (9.543> 1.985). Service quality had a significant effect on consumer purchasing decisions by 44.5%, the hypothesis test obtained t count> t table or (8.824> 1.985). Promotion and service quality simultaneously had a significant effect on consumer purchasing decisions with the regression equation Y = 7.153 + 0.442X1 + 0.391X2 and a contribution of 62.0%, the hypothesis test obtained F count> F table or (78.337> 2.700).